Training of representatives of the family health strategy for the application of the standard operating procedure for systemic arterial hypertension in the municipality of São Caetano do Sul (Research, Society and Development, 2023)
Monitoring patients with Systemic Arterial Hypertension (SAH) is an elementary part of the routine activities of primary health care. In this sense, professionals must be trained to identify new carriers, as well as preserve the monitoring of patients already diagnosed, the in order to maintain continuity of care. This work aimed to train the nursing team and community agents through a document called standard operating procedure (sop) in a continuing training and health education project. A qualitative exploratory field research was carried out to investigate the possibility of applying the sah pop in the municipality of São Caetano do Sul – SP, in order to associate it with the literature review that would better allow assertiveness both in the elaboration of the pop tool, and in the process of presentation and conversion into a health access instrument. After collecting the results, the study considered that the sequencing of documentary implementation for the training of health teams is viable and considers it to be a significant contribution to the health and care process in primary health care.